Effect of preparations on the sowing quality of spring barley (Hordeum vulgare L.) seeds and grain yield - Kuzmenko, N.V.; Popov, S.I.; Hutianskyi, R.A.; Avramenko, S.V.; Hlubokyi, O.M.; Skydan, V.O. (Quarantine and plant protection, 2025)
Goal. To study the sowing qualities of spring barley seeds depending on pre-sowing treatment with a biopreparation, as well as fungicidal and insecticidal preparations from different chemical groups and their mixtures. Methods. The research was conducted in a nine-field fallow-grain-row crop rotation at the Department of Plant Production and Variety Study of the V.Ya. Yuriev Institute of Plant Production of the NAAS of Ukraine (eastern part of the Forest-Steppe of Ukraine) during 2019—2020. Results. The sowing qualities of spring barley seeds were studied depending on pre-sowing treatment with the biopreparation Trichodermin BT, wp (spores of the fungus Trichoderma viride, strain T-4, spore titer 5.0 billion CFU/cm³) and systemic chemical preparations. Under field conditions, the fungicides Insure Perform FS, SC (triticonazole, 80 g/L + pyraclostrobin, 40 g/L), Lamardor 400 FS, SC (prothioconazole, 250 g/L + tebuconazole, 150 g/L), and the biopreparation Trichodermin BT, wp increased germination by 5—7%. The fungicide Vitavax 200 FF, EC (carboxin, 200 g/L + thiram, 200 g/L) and the insecto-fungicide Vibrance Integral 235 FS, SC (sedaxane, 25 g/L + fludioxonil, 25 g/L + tebuconazole, 10 g/L + thiamethoxam, 175 g/L) reduced field germination by 9% and 5%, respectively. In the control (without seed protection), field germination was 91%. In the variant with the application of organo-mineral fertilizers and pre-sowing seed treatment with the insecto-fungicide Yunta Quattro 373.4 FS, SC (prothioconazole, 33.3 g/L + tebuconazole, 6.7 g/L + imidacloprid, 166.7 g/L + clothianidin, 166.7 g/L), the preserved grain yield was 0.75 t/ ha. Conclusions. The influence of the biological preparation and seed treatments with different chemical compositions on germination energy, laboratory and field germination, lodging resistance under field conditions, and the yield of spring barley grain was established.